1998
DOI: 10.1093/annonc/9.suppl_5.s31
|View full text |Cite
|
Sign up to set email alerts
|

Workshop report on Hodgkin’s disease and related diseases (‘grey zone’ lymphoma)

Abstract: Despite advances in immunohistochemistry and molecular biology, the distinction between classical Hodgkin's lymphoma and related diseases such as nodular lymphocyte-predominant Hodgkin's disease, T-cell rich large B-cell lymphoma or anaplastic large cell lymphoma has remained difficult in rare cases. Lack of clear-cut diagnostic criteria represents a problem for both the pathologist and the clinician. To delineate this 'grey zone' between classical Hodgkin's lymphoma and non-Hodgkin's lymphoma (NHL) and to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 18 publications
2
84
0
2
Order By: Relevance
“…These represent cytotoxic T-lymphocytes with some nuclear atypial similar to those found in the inflammatory background infiltrate of T cell rich B-cell lymphoma. 51 These results are comparable to those of Nakamura et al 23 Interestingly, only 50% of the cases proved to be clonal by PCR in these CD8-dominant cases, although 71% were positive among the CD4-dominant ones.…”
Section: All Ailt Are Derived From Cd4 ϩ T-lymphocytessupporting
confidence: 85%
“…These represent cytotoxic T-lymphocytes with some nuclear atypial similar to those found in the inflammatory background infiltrate of T cell rich B-cell lymphoma. 51 These results are comparable to those of Nakamura et al 23 Interestingly, only 50% of the cases proved to be clonal by PCR in these CD8-dominant cases, although 71% were positive among the CD4-dominant ones.…”
Section: All Ailt Are Derived From Cd4 ϩ T-lymphocytessupporting
confidence: 85%
“…In accordance with these findings, some authors described the presence of so-called 'grayzone' lymphomas, showing features intermediate between classical nodular-sclerosis Hodgkin's lymphoma and primary mediastinal large B-cell lymphoma. 24,25 Starting from this background, we demonstrated that TP73L really functioned as a watershed between the two related entities, because all primary mediastinal large B-cell lymphoma were TP73L-positive, while all classical Hodgkin's lymphoma were negative. Notably, in addition to primary mediastinal large B-cell lymphoma, TP73L appeared to be expressed in nearly all nodular lymphocyte-predominant Hodgkin's lymphoma, but not in classical Hodgkin's lymphoma.…”
Section: Discussionmentioning
confidence: 85%
“…These papers also highlighted unexpected similarities between primary mediastinal large B-cell lymphoma and Hodgkin's lymphoma; in accordance with these findings, some authors described the presence of 'gray-zone' lymphomas presenting features intermediate between primary mediastinal large B-cell lymphoma and mediastinal classical Hodgkin's lymphoma. 24,25 TP73L (as defined by the HUGO nomenclature; also known as p63) is a member of the TP53 family, which also includes TP53 itself and TP73. [26][27][28] Unlike TP53, the TP73L gene has two transcriptional starting sites (giving rise either to the transactivating (TA) or to the N-deleted (DN) variants) and its mRNA undergoes complex differential splicing, thus giving rise to at least six different molecular species with different biologic activities.…”
mentioning
confidence: 99%
“…As the prototypic cytomorphology of HRS cells is shared by transformed large B lymphocytes, especially those harboring EBV, a biologic overlap between HL and NHL does exist. It is tempting to speculate that EBV-positive CHL and EBV-positive B-cell LPD may constitute a continuous spectrum of disease 15 . Further studies, however, are required to understand in detail the clinicopathologic profiles, the immunology, the molecular biology, and the therapeutic strategies for treatment of these diseases.…”
Section: Discussionmentioning
confidence: 99%